2010
DOI: 10.1097/eja.0b013e328338d56b
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of premature epidural catheter termination as a quality indicator in a developing country

Abstract: Identification of premature epidural catheter termination as a quality indicator and continuous quality improvement efforts later on proved to be a useful approach in reducing the incidence. The present audit also helped to quantify the improvement in the quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
3
5
0
Order By: Relevance
“…Previous studies have reported disconnection rates in the range of 1.7-2.3% [4,19,20]; these rates were comparable with the rate in this study's old group, which was 1.9%. In the clinical study, there was a signi cant difference in disconnection rates among the groups; speci cally, these rates were highest in the new group and lowest in the taping group.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Previous studies have reported disconnection rates in the range of 1.7-2.3% [4,19,20]; these rates were comparable with the rate in this study's old group, which was 1.9%. In the clinical study, there was a signi cant difference in disconnection rates among the groups; speci cally, these rates were highest in the new group and lowest in the taping group.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have reported dislodgement rates in the range of 1.2-5.1% [4,19,20]. The present rates were comparable with or lower than those previously reported, suggesting that this approach may be bene cial.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Epidural analgesia (EA) is effective and helps improve post-surgical morbidity and hospitalization outcomes [ 1 3 ]. EA is associated with the risk of complications and adverse events, such as accidental epidural catheter removal, including catheter dislodgement and disconnection, post-dural puncture headache, local anesthetic toxicity, and epidural abscess or hematoma formation [ 4 ]. Although accidental epidural catheter dislodgement and disconnection are minor complications, they could be associated with the catheter, connector, and filter themselves rather than patient- or staff-related factors [ 5 10 ].…”
Section: Introductionmentioning
confidence: 99%